History and temperature dependent cyclic crystal plasticity model with material-invariant parameters - Ashraf, Farhan; Castelluccio, Gustavo M. (Elsevier, 2023)
Cyclic deformation of metallic materials depends on the interaction of multiple mechanisms across different length scales. Solid solution atoms, vacancies, grain boundaries, and forest dislocations interfere with dislocation glide and increase the macroscopic strength. In single phase metallic materials under cyclic loading, the localization of dislocation densities in sessile substructures explains a significant fraction of the strain hardening. Upon cycling, these dislocation structures evolve across stable configurations, which depend on the strain accumulation. This work advances substructure-sensitive crystal plasticity models capable of quantifying the cyclic hardening history at various temperatures for single phase FCC materials. The framework predicts the cyclic evolution of dislocation substructure based on the activation of cross slip activation for Al, Cu, and Ni single- and poly-crystals up to 0.5 homologous temperature. The increase in cross slip with temperature and deformation induces a transformation in dislocation structures, which predicts secondary hardening without any additional provision. Moreover, the approach relies on material-invariant mesoscale parameters that are specific to dislocation substructures rather than a material system. Hence, we demonstrate that crystal plasticity predictive power can be augmented by parameterizing the model with single crystal experimental data from multiple materials with common substructures. As a result, the crystal plasticity model shares parameter information across materials without the need for additional single crystal experimental data for calibration.
Keywords: Cyclic deformation; FCC metallic materials; Mesoscale dislocation substructures; Single crystal